Resolving Cell Fate Decisions during Somatic Cell Reprogramming by Single-Cell RNA-Seq - Guo, Lin; Lin, Lihui; Wang, Xiaoshan; Gao, Mingwei; Cao, Shangtao; Mai, Yuanbang; Wu, Fang; Kuang, Junqi; Liu, He; Yang, Jiaqi; Chu, Shilong; Song, Hong; et al. (Molecular cell, 2019)
Somatic cells can be reprogrammed into induced pluripotent stem cells (iPSCs), which is a highly heterogeneous process. Here we report the cell fate continuum during somatic cell reprogramming at single-cell resolution. We first develop SOT to analyze cell fate continuum from Oct4/Sox2/Klf4- or OSK-mediated reprogramming and show that cells bifurcate into two categories, reprogramming potential (RP) or non-reprogramming (NR). We further show that Klf4 contributes to Cd34+/Fxyd5+/Psca+ keratinocyte-like NR fate and that IFN-γ impedes the final transition to chimera-competent pluripotency along the RP cells. We analyze more than 150,000 single cells from both OSK and chemical reprograming and identify additional NR/RP bifurcation points. Our work reveals a generic bifurcation model for cell fate decisions during somatic cell reprogramming that may be applicable to other systems and inspire further improvements for reprogramming. [Display omitted] •Cell fate continuum generated by somatic reprogramming•Single-cell Orientation Tracing (SOT) for fate trajectory detection•Two non-reprogramming trajectories regulated by Klf4 and IFN-γ•A generic bifurcation model for cell fate decisions Guo et al. report the cell fate continuum during induced pluripotent stem cell (iPSC) reprogramming at single-cell resolution. By developing SOT as a new analytic tool, they identify several previously unknown bifurcation points along the reprogramming path and propose a generic bifurcation model for cell fate decisions.